2017
DOI: 10.1038/s41598-017-02199-w
|View full text |Cite
|
Sign up to set email alerts
|

High-efficiency broadband second harmonic generation in single hexagonal GaAs nanowire

Abstract: In this paper, we investigate second harmonic generation in a single hexagonal GaAs nanowire. An excellent frequency converter based on this nanowire excited using a femtosecond laser is demonstrated to operate over a range from 730 nm to 1960 nm, which is wider than previously reported ranges for nanowires in the literature. The converter always operates with a high conversion efficiency of ~10−5 W−1 which is ~103 times higher than that obtained from the surface of bulk GaAs. This nanoscale nolinear optical c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
6
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 39 publications
(52 reference statements)
1
6
1
Order By: Relevance
“…Extensive examination of our experimental data revealed that the intensity of the minor plasmon mode often rapidly decreased to zero upon rotation of the polarization to the vertical direction. This polarization dependence is in good agreement with previous investigations and theoretical expectations for SHG. The schematic illustration in Figure a is in the case of θ = 24° and φ = 0°, depicts the differences of the electric field and its z -component distribution between the front and back surfaces. This filed distribution is also in good agreement with those of previous works on SHG in nanorods and nanowires. , The periodicity of the minor modes is almost half that of the major mode.…”
supporting
confidence: 90%
“…Extensive examination of our experimental data revealed that the intensity of the minor plasmon mode often rapidly decreased to zero upon rotation of the polarization to the vertical direction. This polarization dependence is in good agreement with previous investigations and theoretical expectations for SHG. The schematic illustration in Figure a is in the case of θ = 24° and φ = 0°, depicts the differences of the electric field and its z -component distribution between the front and back surfaces. This filed distribution is also in good agreement with those of previous works on SHG in nanorods and nanowires. , The periodicity of the minor modes is almost half that of the major mode.…”
supporting
confidence: 90%
“…9,10 Surface nonlinearity has only been reported at the core-cladding interface of pure silica OFNs. This is different from the case of conventional doped single-mode optical fiber, which could be poled or was observed with second-order susceptibility χ (2) grating through multiphoton processes. In 2007, efficient second harmonic generation (SHG) was observed in OFNs with an estimated interaction length of only 100 μm.…”
contrasting
confidence: 77%
“…A vast variety of nanowires have been fabricated from diverse materials using a wide range of bottom-up techniques such as chemical vapor deposition and top-down processes such as electron beam lithography and optical fiber drawing. Optical fiber nanowires (OFNs) fabricated via top-down processes have inherent pigtails and can have low-loss interconnection to other common optical fibers and components, which are different from other nanowires of other materials that require bulky lens assemblies to couple input/output light. , Since the great progress made in the fabrication of low-loss OFNs in 2003, they have been widely investigated and are considered as elemental building blocks for future miniature all-fiber circuits. This is because of their unique optical and mechanical properties that include strong optical field confinement, a large evanescent field, as well as excellent configurability .…”
mentioning
confidence: 99%
“…4 The high γ factor in our cavity comes in part due to the high χ (2) factor of GaAs, however, it is much higher (2 orders) than the systems like GaAs nanowire structures. 28 These advantages, apart from the passivation problem in such structures, can be observed without more complex cavity engineering to control the fundamental (w) and the SHG field (2w) phases in the cavity. [8][9][10]29 The SHG-polariton process has a dynamic relationship with the polariton intensity emission, together with the Kerr effect or TPA, 10 bistability, 11,12,20 and squeezing.…”
Section: ■ Discussionmentioning
confidence: 99%